Molecular diagnostics of CNS embryonal tumors - Pfister, Stefan; Korshunov, Andrey; Kool, Marcel; Hasselblatt, Martin; Eberhart, Charles; Taylor, Michael D. (Acta neuropathologica, 2010)
Tremendous progress has recently been made in both molecular subgrouping, and the establishment of prognostic biomarkers for embryonal brain tumors, particularly medulloblastoma. Several prognostic biomarkers that were initially identified in retrospective cohorts of medulloblastoma, including MYC and MYCN amplification, nuclear β-catenin accumulation, and chromosome 17 aberrations have now been validated in clinical trials. Moreover, molecular subgroups based on distinct transcriptome profiles have been consistently reported from various groups on different platforms demonstrating that the concept of distinct medulloblastoma subgroups is very robust. Well-described subgroups of medulloblastomas include tumors showing wingless signaling pathway (Wnt) activation, and another characterized by sonic hedgehog pathway activity. Two or more additional subgroups were consistently reported to contain the vast majority of high-risk tumors, including most tumors with metastatic disease at diagnosis and/or large cell/anaplastic histology. Several years ago, atypical teratoid rhabdoid tumor (AT/RT) was recognized as a separate entity based on its distinct biology and particularly aggressive clinical behavior. These tumors may occur supra or infratentorially and are usually found to have genetic alterations of SMARCB1 (INI1/hSNF5), a tumor suppressor gene located on chromosome 22q. Subsequent loss of SMARCB1 protein expression comprises a relatively specific and sensitive diagnostic marker for AT/RT. For CNS primitive neuroectodermal tumors (CNS PNETs), a consistent finding has been that they are molecularly distinct from medulloblastoma. Furthermore, a distinct fraction of CNS PNETs with particularly poor prognosis only occurring in young children was delineated, which was previously labeled ependymoblastoma or embryonal tumor with abundant neuropil and true rosettes (ETANTR) and which is morphologically characterized by the presence of multilayered “ependymoblastic” rosettes. This group of tumors shows a unique cytogenetic abnormality not seen in other brain tumors: focal amplification of a micro-RNA cluster at chromosome 19q13.42, which has never been found to be amplified in other CNS PNETs, medulloblastoma or AT/RT. In summary, these consistent findings have significantly contributed to our ability to sub-classify embryonal brain tumors into clinically and biologically meaningful strata and, for some of the subgroups, have led to the identification of specific targets for future development of molecularly targeted therapies.
Gesehen am 02.05.2023